METAFORA : LEGISLATOR MAKASSAR LIVE BY (GEORGE LAKOFF AND MARK JOHNSON) - Ernyanti Zain (PROGRESS, 2014)
The use of metaphor is one of the most prominent tools for persuasion and an instrument for propaganda in political speech. This study aimed at: (1) identifying metaphorical expressions used by Makassar legislators in speech, (2) finding out the kinds of conceptual metaphors formulated from the metaphorical expressions. This research was conducted in DPRD Makassar, South Sulawesi. This was a descriptive research by using qualitative approach. Methods used in collecting data were recording and transcribing. The number of samples was seven speeches delivered by politicians in General View Presentation. The result of this research indicates that Makassar legislators conceptualize regulations as flats, people, and food products; taxes as waves and cargoes; appreciation is oriented as up and togetherness is oriented as front